Respuesta :

r3t40
Hi,

Solving:

[tex]20 - 7x = 7x + 13 \\ - 7x - 7x + 20 = 7x - 7x + 13 \\ - 7x - 7x + 20 = 13 \\ - 7x - 7x = 13 - 20 \\ ( - 7 - 7)x = - 14x \\ - 14x = 13 - 20 \\ - (20 - 13) = - 7 \\ - \not14x \div ( - \not14) = - 7 \div ( - 14) \\ x = -7 \div ( - 14) \\ ( - ) \div ( - ) = ( + ) \: \: \: \: \: \: \: rule \\ x = 7 \div 14 = \frac{1}{2} = 0.5[/tex]

Equation haves a solution.

Hope this helps you understand your question better.

If you posses any additional questions you are welcome to comment below.

r3t40